Compression map: Improved means for studying Carboniferous foliage - Zodrow, Erwin L. (2013)
A medullosalean-pteridosperm specimen, 22 cm long, from the Sydney Coalfield, Nova Scotia, Canada, illustrates the advantage of studying the fossilization history of compressed foliage freed from the rock matrix by hydrofluoric acid, as compared to the examination of compressions still in the rock matrix. The image of any freed frond segment of compression foliage that has been reprocessed digitally to represent its original structure is called a compression map. Interpretation of a compression map is reliant on a physicogeochemical model of preservation processes.